2020
DOI: 10.1038/s41389-020-0197-0
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin sulfate synthase 1 enhances proliferation of glioblastoma by modulating PDGFRA stability

Abstract: Chondroitin sulfate synthases, a family of enzyme involved in chondroitin sulfate (CS) polymerization, are dysregulated in various human malignancies, but their roles in glioma remain unclear. We performed database analysis and immunohistochemistry on human glioma tissue, to demonstrate that the expression of CHSY1 was frequently upregulated in glioma, and that it was associated with adverse clinicopathologic features, including high tumor grade and poor survival. Using a chondroitin sulfate-specific antibody,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…We have previously demonstrated that CHSY1 functions as the dominant CS synthase in human glioma cells, and its expression is significantly correlated with the anti-CS antibody (CS56) staining intensity in glioma tissues [ 17 ]. Thus, to explore the CS-associated pathways in human GBM, we analyzed genes co-expressed with CHSY1 in the TCGA dataset using the cBioPortal for cancer genomics [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that CHSY1 functions as the dominant CS synthase in human glioma cells, and its expression is significantly correlated with the anti-CS antibody (CS56) staining intensity in glioma tissues [ 17 ]. Thus, to explore the CS-associated pathways in human GBM, we analyzed genes co-expressed with CHSY1 in the TCGA dataset using the cBioPortal for cancer genomics [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies have identified that CHSY1 is frequently upregulated in tumor tissues such as human glioma and hepatocellular carcinoma. Moreover, the upregulation of CHSY1 not only enhances CS formation on cancer cells, but is also positively associated with poor patient outcomes [ 16 , 17 ]. However, the specific CSPGs involved in the CHSY1-regulated malignant phenotypes of cancer cells are yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, using the TGF-β type I receptor kinase inhibitor, LY364947 successfully reversed CHPF-silencing-enhanced cell viability, cell migration, and invasion (Figure 5B,C), suggesting that TGF-β signaling participates in CHPF-regulated malignancy of HCC cells. CS synthases-remodeled CS proteoglycans (CSPGs) are crucial for modulating signal transduction and cell-cell communication [21,23,34], and CSPG DCN is known to be a key regulator of TGF-β signaling [35][36][37]. Thus, we examined the influence of CHPF on DCN in HCC cells.…”
Section: Chpf Modulates Tgf-β Signaling and Modifies The Cs Chains Of Decorin (Dcn)mentioning
confidence: 99%
“…Several recent studies have revealed that these CS synthases and CS-modifying enzymes show tissue-specific expression profiles and play distinct roles in regulating the malignant behaviors of cancer cells. For instance, CHSY1 was upregulated in HCC and glioma tissues, and its upregulation was associated with poor outcomes in patients [20,21]. The CS epimerase DSE is also frequently upregulated in human gliomas, and its increased expression is typically associated with worse prognoses [22].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, a recent study indicated that lncRNA PVT1 was highly expressed in GC tissues and can promote tumor progression by interacting with FoxM1, and PVT1 [ 18 ]. Furthermore, Xiao et al reported that lncRNA TRPM2-AS exerted a pro-tumor effect by sponging miR-612 in GC cells [ 19 ]. In addition, there are many other dysregulated lncRNAs involved in GC progression, such as LINC00152, PANDA, MAGI2-AS3, PWRN1 and TUBA4B [ 20 ].…”
Section: Introductionmentioning
confidence: 99%